Factors Affecting Undergraduate Students Academic Failure in Kerman University of Medical Sciences Iran; A CaseControl Study - Mahshid Loloie; Ali Akbar Haghdoost; Ali Akbar Haghdoost; Azam Bazrafshan; Maryam Okhovati; Ali Mohammad Mokhtari; Morteza Zare (Kerman University of Medical Sciences, 2017)
Background & Objective: academic failure has always been one of the major challenges of higher education institutions that could cause serious individual and social outcomes This study aimed to analysis the effect of potential factors on students academic failure in Kerman University of Medical Sciences Iran Methods: This was an unmatched casecontrol study The study population consisted of all undergraduate students of Kerman University of Medical Sciences in two semesters in 2012 From 514 selected students 246 were assigned to the case group and the rest were studied in the control group Data were collected using a selfadministered questionnaire via consensus methodology The questionnaire consisted of three sections: individual family and academic factors Reliability of the questionnaire was approved by a group of faculty members and its internal consistency was estimated as 082 Data were analyzed using SPSS software Results: The mean age of studied students was 222 years The mean grade point average (GPA) of was 142 and 169 in cases and controls respectively Academic failure was 164 times more in boys than the girls (P = 002) and 159 times more in students who had a sense of frustration (P = 002) Students who reported using drugs tobacco or alcohol experienced academic failure 639 times more than the others (P = 001) Conclusion: Academic failure is a phenomenon affected by multiple factors Therefore reducing it requires the participation of a wide range of people taking part in students learning